Waterbird use of farm dams in south-eastern Australia: abundance and influence of biophysical and landscape characteristics. Issue 1 (December 2017) - Hamilton, Andrew; Conort, Chloé; Bueno, Aurore; Murray, Christopher; Grove, James
Abstract Background While agriculture has taken much environmental water in Australia's Murray-Darling Basin, agricultural expansion has resulted in a vast number of farm dams, almost three-quarters of a million in the Murray-Darling Basin alone. Methods Over a summer we studied (1) waterbird abundance and species richness and (2) the influence of biophysical and landscape characteristics across 49 farm dams at a large mixed-enterprise farm in northern Victoria on the southern reach of the Murray-Darling Basin. Results On average, dams were found to host 27.1 ± 71.1 individuals/ha and 1.8 ± 2.9 species per pond. Such densities are comparable to those on natural wetlands. Dam surface area and perimeter and amount of vegetation were positively and strongly correlated with the Rallidae density (birds/ha), but no other parameters were strongly correlated with any other functional group. The landscape in which the dams were embedded had a highly significant effect (p  < 0.001) on the number of birds found on a dam. Conclusions Our research needs to be complemented with further studies in other parts of the Basin and on other taxa, but given at our site they supported similar densities of individuals and species to natural wetlands, and given the fact that there are 710, 539 farm dams in the Murray-Darling Basin, which hosts much of Australia's waterbird fauna, it is reasonable to suggest that farm dams are overlooked, and possibly very important, avian biodiversity hotspots. It also highlights the importance of a landscape setting, in which dams are situated, on the number of birds using the dams.